Anatomical Pathways for Auditory Memory in Primates - Monica Munoz-Lopez; Alicia MohedanoMoriano; Ricardo Insausti (Frontiers Media S.A., 2010)
Episodic memory or the ability to store context-rich information about everyday events depends on the hippocampal formation (entorhinal cortex, subiculum, presubiculum, parasubiculum, hippocampus proper, and dentate gyrus). A substantial amount of behavioral-lesion and anatomical studies have contributed to our understanding of the organization of how visual stimuli are retained in episodic memory. However, whether auditory memory is organized similarly is still unclear. One hypothesis is that, like the ‘visual ventral stream’ for which the connections of the inferior temporal gyrus with the perirhinal cortex are necessary for visual recognition in monkeys, direct connections between the auditory association areas of the superior temporal gyrus and the hippocampal formation and with the parahippocampal region (temporal pole, perhirinal, and posterior parahippocampal cortices) might also underlie recognition memory for sounds. Alternatively, the anatomical organization of memory could be different in audition. This alternative ‘indirect stream’ hypothesis posits that, unlike the visual association cortex, the majority of auditory association cortex makes one or more synapses in intermediate, polymodal areas, where they may integrate information from other sensory modalities, before reaching the medial temporal memory system. This review considers anatomical studies that can support either one or both hypotheses – focusing on anatomical studies on the primate brain that have reported not only direct auditory association connections with medial temporal areas, but, importantly, also possible indirect pathways for auditory information to reach the medial temporal lobe memory system.